Penarapan Algoritma Prefix Code Dalam Kompresi File Video - Alfarizi, Muhammad; Aripin, Soeb; Zebua, Taronisokhi (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2020)
Data compression technology is the process of converting a set of data into a lower coded representation of data that is not encoded with a certain encoding. Data compression is done by encoding each character into a shorter coded message, in order to save storage space requirements and time for data transmission. Compressing is used to speed up the sending process from uncoded characters to certain encoded characters. By compressing, large data will be reduced in size so as to save storage capacity. In this study, using the Prefix Code algorithm, by using this method the compression results are very good in making data transmission and transferring video file allocations easier and faster. By doing compression, large data will be reduced in size so that it can save storage space. There are many types of methods or algorithms in video file compression, but in this algorithm the writer only wants to know the compression process using the Prefix Code algorithm using the C1 code where the author has successfully compressed a video file with the prefix code algorithm using the C1 code has the ability to compress video file 37, 5% on a video file.Keywords: Compression, Video, File, Prefix Code, Algorithm.